Kepribadian Ekstrovert Dan Introvert Dalam Hubungan Persahabatan Melalui Pendekatan Komunikasi - Kusumadinata, Ali Alamsyah; Hardiyanti, Putri (HUMANUS : Jurnal Sosiohumaniora Nusantara, 2023)
The formulation of the problem in this study is "How is interpersonal communication on introvert and extrovert personalities in establishing friendly relations". This study uses a qualitative method. The key informant in this study was a counseling teacher who had an educational background in psychology, and a supporting informant from the Alumni Association of SMK Negeri 3 Bogor who had extroverted and introverted personality types. The results show that each personality type (extrovert and introvert) has its own way of establishing friendly relations through interpersonal communication approaches. Aspects of interpersonal communication include equality which refers to equalizing the circumstances and degrees of communication. Furthermore, the aspect of openness which in this process can make people who are in a relationship get to know each other and begin to grow trust and emotional feelings. There is also an aspect of a positive attitude, which means always thinking well and making the atmosphere of the relationship always peaceful and harmonious. Then there is the aspect of empathy that is much needed, caring actions are accompanied by verbally shown actions. The last is mutual support which is the most important aspect so that a friendly relationship avoids problems that can lead to destruction. The friendly relationship that is forged by each extrovert and introvert personality has stages. The first stage starts with contact (getting acquainted with each other), the involvement stage (getting each other's first impressions), the familiarity stage (getting to know more deeply), the destruction stage (when a crisis occurs, there are problems in friendly relations), the termination stage (disconnection can occur). relationship if the problem at hand cannot be resolved). All aspects of interpersonal communication and these stages occur in the process of establishing friendly relations in each extrovert and introvert personality type.